EMPOWERMENT OF COASTAL WOMEN COMMUNITY OF GAMPONG PUSONG LAMA THROUGH INNOVATION OF MARINE PROCESSED PRODUCTS - Likdanawati, Likdanawati; Hamdiah, Hamdiah; Putri Mellita, Cut (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2021)
The Lhokseumawe City Government consists of 4 (four) sub-districts, namely Muara Dua District, Muara Satu District, Blang Mangat District and Banda Sakti District. The old Pusong Village is one of the villages located in Banda Sakti District. Gampong Pusong Lama is one of the villages located on the coast of the city of Lhokseumawe, and the average population of Gampong Pusong is whose income depends on the catch of fish. The catch of fishermen is affected by the wind. If the wind is strong then their catch is small and this has an impact on fishermen's income. Under these circumstances, fishermen can only surrender and use a small amount of their past income to meet their daily needs. Fish caught by fishermen have high nutritional and protein content. The fishermen's family members consume the caught fish every day by cooking it as a side dish. Whereas in addition to being cooked as a side dish, fish can also be processed into ready-to-eat food and can increase its economic value. They still have minimal knowledge about the technology of processing fishery products other than being cooked into side dishes. Fishermen's family members, namely fishermen's mothers, have the potential to improve the economic conditions of their families. Given these conditions, it is necessary to make an effort to improve the economy and skills with science and technology. For this reason, it is necessary to make an effort to empower fishing communities, especially women in an effort to increase the income of fishermen's families. The purpose of this Community Service Activity (PKM) is to empower the community by using science and technology to improve the skills and economic income of partners through processing marine products in the form of fish. the processing does not require modern equipment, (2) training and assistance in the manufacture of modern fishery products that are rich in nutrition. (3) product packaging. The result of this activity is the increased knowledge and skills of partners in processing fishery products. The method of carrying out activities is carried out by (1) introducing nutritious modern fishery products whose processing does not require modern equipment, (2) training and assistance in the manufacture of modern fishery products that are rich in nutrition. (3) product packaging. The result of this activity is the increased knowledge and skills of partners in processing fishery products. The method of carrying out activities is carried out by (1) introducing nutritious modern fishery products whose processing does not require modern equipment, (2) training and assistance in the manufacture of modern fishery products that are rich in nutrition. (3) product packaging. The result of this activity is the increased knowledge and skills of partners in processing fishery products.